2009
DOI: 10.1016/j.brainres.2008.09.094
|View full text |Cite
|
Sign up to set email alerts
|

Proximal colon distension induces Fos expression in oxytocin-, vasopressin-, CRF- and catecholamines-containing neurons in rat brain

Abstract: Little is known about the chemical coding of the brain neuronal circuitry activated by nociceptive signals of visceral origin. We characterized brain nuclei activated during isovolumetric phasic distension of the proximal colon (10 ml, 30 s on/off for 10 min) in conscious male rats, using Fos as a marker of neuronal activation and dual immunohistochemistry to visualize co-localization of Fos expression and oxytocin (OT), arginine-vasopressin (AVP), corticotrophin-releasing factor (CRF) or tyrosine hydroxylase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 80 publications
(115 reference statements)
7
43
0
1
Order By: Relevance
“…Fos-IR nuclei in the VLM were found in the entire rostral-caudal column including the C1/A1 cell groups, and the number of the Fos-IR nuclei was significantly different in nonstressed rats and rats exposed to RWIS for 1 h, in agreement with results for proximal colon distension in rats [20].…”
Section: Psychological and Physical Stressors Induce Activation Of DIsupporting
confidence: 88%
See 2 more Smart Citations
“…Fos-IR nuclei in the VLM were found in the entire rostral-caudal column including the C1/A1 cell groups, and the number of the Fos-IR nuclei was significantly different in nonstressed rats and rats exposed to RWIS for 1 h, in agreement with results for proximal colon distension in rats [20].…”
Section: Psychological and Physical Stressors Induce Activation Of DIsupporting
confidence: 88%
“…Many previous studies have found that CA-neurons of the MVZ were involved in processing and conducting visceral nociceptive information. Proximal colon distension induced Fos in approximately 74 and 42% of CA-neurons in the VLM and the NTS, respectively [20]. RWIS induced substantial Fos protein expression in noradrenergic neurons of the MVZ (A1/A2 cell groups) [43].…”
Section: Psychological and Physical Stressors Induce Activation Of DImentioning
confidence: 98%
See 1 more Smart Citation
“…This deduction is consistent with the results published by others who found no evidence of an increase in MPO levels or histological damage or inflammatory infiltrate after 1-h repetitive CRD at 60 mmHg in rat (22) or mouse (24) colon. Similarly, Wang et al (48) reported that repeated CRD in healthy rats at 78 -100 mmHg activated certain hypothalamic brain nuclei 1 h after CRD cessation; no inflammation was reported that might have evoked the brain activity.…”
Section: Discussionmentioning
confidence: 91%
“…The use of C-Fos expression as a marker of neuronal activation has shown that somatovisceral Sinniger, et al 2004;2005), and visceral (Wang, et al 2009) pain as well as stress-or abdominal surgery-induced GI disturbances (Bonaz and Tache 1994a;1994b;1997;Bonaz and Rivest 1998) and colitis ) induced the activation of the amygdala. In addition, the amygdala is one of the central areas from where digestive sensations are elicited in epileptic patients (Mulak, et al 2008) during intracerebral electrical stimulations.…”
Section: Amygdala and Visceral Hyperalgesiamentioning
confidence: 99%